Book review: "Asian studies in Spain: Analysis, evolution and perspectives" by Raúl Ramírez Ruiz, Cristina del Prado Higuera and Felipe R. Debasa Navalpotro. Navarra: Editorial Aranzadi/Universidad Rey Juan Carlos, 2023. 384 pages. ISBN: 978-84-1124-933-1 (Sinología hispánica. China Studies Review, 2025)
No hay resumen